Разработка технологии получения силикагелей из диатомита и других кремнийсодержащих материалов - Зубков, Александр Вадимович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In the present study, the technology for producing powdered and lumpy silica from diatomite has been developed. The most energy-intensive stages of the domestic technology are excluded: high-temperature sintering of quartz sand with soda and autoclave dissolution of a silicate block. Also, the developed technology makes it possible to obtain silica-gels, which in terms of their qualities (sorption capacity, textural characteristics) can compete with imported ones. The innovation of developed technology is based on the use of diatomite as a raw material. The diatomite is a sedimentary rock consisting of silicon oxide shells of diatomite microorganisms. The porous structure of raw diatomite was characterized by low-temperature nitrogen adsorption (–196 ºC) and scanning electron microscopy (SEM). The prepared liquid glass from diatomite and other silicon-containing materials was used for the synthesis of silica. The effect of pH precipitation on the properties of the resulting silica was studied.